A study on knowledge regarding different aspects of injection safety among injection providers at different levels of health care - Allaqband, Uroosa Farooq; Fazili, Anjum B.; Shah, Rohul Jabeen; Ganai, Ab. Majid; Balwan, Walied K.; Wani, Feroz (International Journal Of Community Medicine And Public Health, 2017)
Background: Estimates suggest that at least 50% of the world’s injections administered each year are unsafe, particularly in developing countries. Unsafe injection practices put patients and healthcare providers at risk of infectious and non-infectious adverse events, sound knowledge of healthcare providers is vital to break the chain of blood borne diseases transmission caused by unsafe injection practices. Methods: Cross sectional observational questionnaire based study was carried out amongst 152 injection providers of 40 healthcare facilities of two districts of Kashmir valley (one rural and one urban) selected purposively. Results are summarised and presented in the form of tables and chi (x2) test was used for test of association with statistical significance set at p-value of less than 0.05. Results: In this study out of 152 injection providers, majority (81.57%) were in the age range of 21-40 years and 74.3% were females. 43.4% of the participants were FMPHWs, 30.9% were nurses and 13.8% pharmacists. Overall 65.8% and 67.1% of injection providers had correct knowledge regarding WHO definition of safe injection and infections transmitted by unsafe injections respectively. Majority (90.8%) were aware about the biomedical waste management rules. Conclusions: We conclude that over all the knowledge of different aspects of injection safety was good among the participants except the poor knowledge ofpost exposure prophylaxis and disposal of injection related waste despite the use of color coded bags at the sites of waste generation.